Viral suppression among children and their caregivers living with HIV in western Kenya. Issue 4 (15th April 2019) - Humphrey, John M; Genberg, Becky L; Keter, Alfred; Musick, Beverly; Apondi, Edith; Gardner, Adrian; Hogan, Joseph W; Wools‐Kaloustian, Kara
Abstract: Introduction: Despite the central role of caregivers in managing HIV treatment for children living with HIV, viral suppression within caregiver–child dyads in which both members are living with HIV is not well described. Methods: We conducted a retrospective analysis of children living with HIV <15 years of age and their caregivers living with HIV attending HIV clinics affiliated with the Academic Model Providing Access to Healthcare (AMPATH) in Kenya between 2015 and 2017. To be included in the analysis, children and caregivers must have had ≥1 viral load (VL) during the study period while receiving antiretroviral therapy (ART) for ≥6 months, and the date of the caregiver's VL must have occurred ±90 days from the date of the child's VL. The characteristics of children, caregivers and dyads were descriptively summarized. Multivariable logistic regression was used to estimate the odds of viral non‐suppression (≥ 1000 copies/mL) in children, adjusting for caregiver and child characteristics. Results: Of 7667 children who received care at AMPATH during the study period, 1698 were linked to a caregiver living with HIV and included as caregiver–child dyads. For caregivers, 94% were mothers, median age at ART initiation 32.8 years, median CD4 count at ART initiation 164 cells/mm 3 and 23% were not virally suppressed. For children, 52% were female, median age at ART initiation 4.2 years, median CD4 values at ART initiation were 15% (age < 5 years) and 396 cells/mm 3 (age ≥ 5 years), and 38% were not virally suppressed. In the multivariable model, children were found more likely to not be virally suppressed if their caregivers were not suppressed compared to children with suppressed caregivers (aOR = 2.40, 95% CI: 1.86 to 3.10). Other characteristics associated with child viral non‐suppression included caregiver ART regimen change prior to the VL, caregiver receipt of a non‐NNRTI‐based regimen at the time of the VL, younger child age at ART initiation and child tuberculosis treatment at the time of the VL. Conclusions: Children were at higher risk of viral non‐suppression if their caregivers were not virally suppressed compared to children with suppressed caregivers. A child's viral suppression status should be closely monitored if his or her caregiver is not suppressed.